Unveiling the potential of Trichoderma harzianum against Heterodera cajani in pigeon pea: impact on cysts, egg and juveniles abundance - Amit Kumar Maurya; Harish Kumar; Vinny John; Hemlata Pant; D. K. Srivastava; Nevin Ahmed; Fadi Baakdah; Rokayya Sami; Alaa Baazeem; Abeer Elhakem; Mohammad Y. Alshahrani; Alaa T. Qumsani; et al. (Egyptian Journal of Biological Pest Control, 2024)
Abstract Background Pigeon pea is affected by the cyst nematode Heterodera cajani limiting the production. H. cajani can be managed by biological agents such as Trichoderma harzianum. Thus, the determination of this experiment was to estimate native strains of T. harzianum isolated from pigeon pea fields in India on population of cyst, eggs and juveniles of H. cajani. Pots experiment was conducted at the playhouse of Sam Higginbottom University of Science and Technology, Prayagraj (UP), India, during the year of 2018–2020. Earthen pots were filled with sterilized soil @ 10 kg/pot for each replicate of the treatments. Ten days before sowing of the pigeon pea seed, about 5000 spores of T. harzianum were amended in to the soil for proper colonization. Fifteen days after seed germination, 200 cysts/pot were inoculated near the root zone of pigeon pea plant. The pots were irrigated when required. Observations were recorded of cyst population, eggs and second juveniles of H. cajani/500gm of pigeon pea rhizospheric soil at 90 days after sowing. Results Among all the isolates of T. harzianum, the treatment (T 7) reduced of cyst population (12), eggs population (234) and juveniles’ population (153) as compared with all other treatments including control at 90 days after sowing of pigeon pea seeds in the year 2018–2019. Similarly, in 2019–2020 reduction in cyst population (11), eggs population (189) and juveniles population (160) was observed at 90 days after sowing in Trichoderma isolates (T 7) as compared to control. Conclusions The findings of this study are very relevant since seven isolates of native T. harzianum were promising to suppress the number of cysts in 79.31 and 83.07%, eggs in 22.00 and 38.83% and juveniles’ population in 17.74 and 20.39% of the nematode H. cajani, besides promoting the pigeon pea plant growth.